2001
DOI: 10.1053/ejvs.2001.1495
|View full text |Cite
|
Sign up to set email alerts
|

Use of the Percutaneous Vascular Surgery Device for Closure of Femoral Access Sites during Endovascular Aneurysm Repair: Lessons from our Experience

Abstract: use of the percutaneous closure device requires very careful patient selection. Preoperative radiological assessment of the ilio-femoral vessels is vital to assess for cacification and tortuosity. High device failure rates can be expected from obese patients and those with scarred groins. When difficulty is encountered during the procedure, there should be a low threshold for conversion to an open groin incision. The device and the method of introduction can be further improved to address some of these issues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
99
0
6

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(107 citation statements)
references
References 7 publications
2
99
0
6
Order By: Relevance
“…Many studies have shown that obesity or morbid obesity, severely or circumferentially calcified CFA, tortuous iliac arteries, large introducer sheath size (larger than 18 F or 20 F), a scarred groin, the presence of a graft in the access artery, and inexperience with the procedure increase the likelihood of technical failures or complications (2,(4)(5)(6)(7). In some studies, these risk factors were exclusion criteria for the use of the percutaneous closure device; in other studies, they were not (6)(7)(8). Obesity or morbid obesity can increase the complication rate of the percutaneous approach, but successful percutaneous treatment of these patients has the advantage of reducing the rate of wound complications, which is high in cases of surgical cutdown in obese patients.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown that obesity or morbid obesity, severely or circumferentially calcified CFA, tortuous iliac arteries, large introducer sheath size (larger than 18 F or 20 F), a scarred groin, the presence of a graft in the access artery, and inexperience with the procedure increase the likelihood of technical failures or complications (2,(4)(5)(6)(7). In some studies, these risk factors were exclusion criteria for the use of the percutaneous closure device; in other studies, they were not (6)(7)(8). Obesity or morbid obesity can increase the complication rate of the percutaneous approach, but successful percutaneous treatment of these patients has the advantage of reducing the rate of wound complications, which is high in cases of surgical cutdown in obese patients.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the artery closure problem was solved by percutaneous artery suture devolopment. However, current percutanous suture devices, especially in obese patients with scarred groins and calcificated iliac arteries, are not safely feasible and percutaneous EVAR still often remains unreliable [16][17][18] . All our percutanous closure failures were in obese patients (false femoral aneurysm developed in one) and calcified CFA 19 .…”
Section: Discussion Conclusionmentioning
confidence: 99%
“…Complete percutaneous EVAR using CFA percutaneous suture systems is feasibile in some patients [16][17][18][19] ( Fig. 6).…”
Section: Percutaneous Proceduresmentioning
confidence: 99%
“…A subsequent study has demonstrated that even larger sheaths could be used if a second Prostar device is deployed at 45° relative to the first device. 5 At the end of the endograft procedure, the previously deployed sutures are used to close the arteriotomy by pushing the knots down to the level of the arteriotomy. A single Prostar XL 10 has been used to close sheaths up to 24F, but most interventionalists would use 2 devices.…”
Section: Closure Devices For Endovascular Interventionsmentioning
confidence: 99%